Interdisciplinary collaboration: addressing global challenges through innovative learning strategies - Restu Adi Nugraha; Dasim Budimansyah; Yadi Ruyadi; Encep Syarif Nurdin; Mufid Hidayat (Himpunan Pengembang Kurikulum Indonesia (HIPKIN), 2024)
In this era of globalization, students in Indonesia face increasingly complex challenges in understanding, addressing, and contributing to global issues. However, the existing curriculum often fails to provide adequate perspectives and skills to tackle these global problems. Therefore, this research aims to provide students with a holistic, practical, and relevant learning experience to address global challenges through a Team-Based Project strategy that integrates compulsory courses in higher education with a global citizenship education approach. Cross-curricular collaboration helps students see the interconnectedness of various disciplines, which is essential in addressing complex global issues. Survey results indicate a variation of views among student groups regarding their understanding of global issues. This innovative learning strategy utilizes principles of behaviorist theory, such as stimulus-response, positive reinforcement, and social interaction, to create an engaging, relevant, and responsive learning environment tailored to students' needs. Through involvement in joint projects focused on global issues, students are stimulated to contribute and take concrete actions in seeking solutions and bringing about positive change on a larger scale. Thus, this learning strategy is expected to enhance students' understanding, skills, and commitment to addressing global challenges in the contemporary era.